Guidelines for various laboratory sections in view of COVID-19: Recommendations from the Indian Association of Pathologists and Microbiologists - Vatsala Misra; Ranjan Agrawal; Harendra Kumar; Asaranti Kar; Usha Kini; Aruna Poojary; Indranil Chakrabarti; Sharada Rai; Anika Singhal; S Vijay Shankar; Jayaram N Iyengar (Wolters Kluwer Medknow Publications, 2020)
Declared as a pandemic by WHO on March 11, 2020, COVID-19 has brought about a dramatic change in the working of different laboratories across the country. Diagnostic laboratories testing different types of samples play a vital role in the treatment management. Irrespective of their size, each laboratory has to follow strict biosafety guidelines. Different sections of the laboratory receive samples that are variably infectious. Each sample needs to undergo a proper and well-designed processing system so that the personnel involved are not infected and also their close contacts. It takes a huge effort so as to limit the risk of exposure of the working staff during the collection, processing, reporting or dispatching of biohazard samples. Guidelines help in preventing the laboratory staff and healthcare workers from contracting the disease which has a known human to human route of transmission and high rate of mortality. A well-knit approach is the need of the hour to combat this fast spreading disease. We anticipate that the guidelines described in this article will be useful for continuing safe work practices by all the laboratories in the country.